Análisis de la problemática surgida con la adopción de facturación electrónica y su efecto en la economía de las empresas - Sanchez Colozuma, Karen Lisseth (2015)
Electronic invoicing is a measure taken by the Ecuadorian Government in order to facilitate the timely delivery of accounting information from companies. This research is developed in order to reduce inconvenience to those companies from the adoption of electronic invoicing. By applying this method was achieved reduce financial and time losses due to misuse of the electronic billing system. The research is based on the use of scientific articles as a method of consultation, generating a wider range of precision and highly acceptable justification for the proposed issue. It should be noted that the qualitative method was used as the sole method of deduction of the existing problem in companies for the development of this project since by this method it describes the processes required to make a correct analysis of the problems in the company. The investigation determined that the existing problem in the company is technical, due to lack of training, lack of updated information from suppliers and customers information which shows a lack of planning by management of the company. After analysis was made concluded that the proposed system does not apply to a company whose number is minimal monthly sales since investment costs are not recoverable in a short span of time. This project is highly beneficial for all those companies that have a range of more than 12 sales monthly sales since the capital recovery time is only 3 months after this time will be significant savings for the company.